Menganalisis Gaya Kepemimpinan pada Era Generasi Milenial - Desri, Syuryatman; Ulfa, Rahmi Datul; Ramadhani, Pia (Lembaga Yasin AlSys, 2023)
In any type of business, leadership is required and plays an important role in the management process. By leading and influencing others, leaders plan and manage available resources to maximize the performance of their subordinates. The leadership approach used and the level of satisfaction among followers both influence how effective a leader is. It is a significant difficulty to develop into effective leaders in the current and future generations of millennial society. Due to tensions and environmental factors at that time, many leaders emerged following the times. Effective administration will be achieved in the millennial generation era if the leader can fulfill the requirements as a credible leader, and has broad capacity, intelligence, and ambition. However, a successful leader must also be honest, have integrity, and be made according to the needs of the people. The independence and energy of the millennial entrepreneurial generation must be supported by millennial leadership. Independence and entrepreneurship are two fundamental pillars that must exist when building a nation.